AUTOCLAVE SYNTHESES OF TETRAPHENYLPORPHYRIN USING VARIOUS OXIDIZING AGENTS - Yustiani Syaban, Itan
Porphyrins are developed for various applications, such as photodynamic therapy agents for cancer and sensitizing materials in solar cells. In this research, synthesis of tetraphenylporphyrin (TPP) was carried out using autoclave with varying oxidizing agent. In an autoclave, the synthesis is performed at high temperature and pressure in a closed and safe condition. Synthesis of tetraphenylporphyrin consists of two steps reactions, namely condensation reaction and oxidation reaction. Oxidizing agents used in this research are the oxygen gas, p-chloranil and acetylene in (acetone). Synthesis with different oxidizing agents produced the same product which shows the characteristics of tetraphenylporphyrin. Results of thin layer chromatography (TLC) with the eluent n-hexane: ethyl acetate = 7: 1 (v / v) shows the results of all three synthesis have the same Rf value of 0.74. UV- visible spectra of three synthesized compounds showed the same absorption features and in accordance with the characteristic of tetraphenylporphyrin, Soret band at 418 nm and four Q bands at 514; 550; 589 and 647 nm. Infrared absorption spectra of synthesized compounds showed absorption at 3318-3320 cm-1 corresponds to N-H vibration; 3130-3132, 3108, and 3075-3078 cm-1 corresponds to C-H vibrations in pyrrole, and absorption at 3054 and 3021-3024 cm-1 which indicate the presence of phenyl vibrations. These three types of vibrational mode are characteristics of tetraphenylporphyrin. 1H NMR spectra of synthesized compounds also shows the presence of pyrrole hydrogen at 8.8 ppm, phenyl hydrogen at 8.2 and 7.7 ppm, as well as the N-H pyrrole hydrogen at -2.7 ppm. These results showed that all three synthesized compounds are tetraphenylporphyrin, with yield of 24.6, 25, and 20% for oxygen, p-chloranil and acetylene, respectively. The yield of synthesis using oxygen and p-chloranil is almost the same, but p-chloranil formed larger of TPP crystallites. In addition, although the yield of reaction using acetylene lower than others, the resulting product was easier to be purified.